p-Hydroxyphenylacetate 3-Hydroxylase as a Biocatalyst for the Synthesis of Trihydroxyphenolic Acids - Taweesak Dhammaraj (2018)
© 2015 American Chemical Society. Trihydroxyphenolic acids such as 3,4,5-trihydroxycinnamic acid (3,4,5-THCA) 4c and 2-(3,4,5-trihydroxyphenyl)acetic acid (3,4,5-THPA) 2c are strong antioxidants that are potentially useful as medicinal agents. Our results show that p-hydroxyphenylacetate (HPA) 3-hydroxylase (HPAH) from Acinetobacter baumannii can catalyze the syntheses of 3,4,5-THPA 2c and 3,4,5-THCA 4c from 4-HPA 2a and p-coumaric acid 4a, respectively. The wild-type HPAH can convert 4-HPA 2a completely into 3,4,5-THPA 2c within 100 min (total turnover number (TTN) of 100). However, the wild-type enzyme cannot efficiently synthesize 3,4,5-THCA 4c. To improve the efficiency, the oxygenase component of HPAH (C2) was rationally engineered in order to maximize the conversion of p-coumaric acid 4a to 3,4,5-THCA 4c. Results from site-directed mutagenesis studies showed that Y398S is significantly more effective than the wild-type enzyme for the synthesis of 3,4,5-THCA 4c; it can catalyze the complete bioconversion of p-coumaric acid 4a to 3,4,5-THCA 4c within 180 min (TTN ∼ 23 at 180 min). The yield and stability of 3,4,5-THPA 2c and 3,4,5-THCA 4c were significantly improved in the presence of ascorbic acid. Thermostability studies showed that the wild-type C2 was very stable and remained active after incubation at 30, 35, and 40 °C for 24 h. Y398S was moderately stable because its activity was retained for 24 h at 30 °C and for 15 h at 35 °C. Transient kinetic studies using stopped-flow spectrophotometry indicated that the key improvement in the reaction of Y398S with p-coumaric acid 4a lies within the protein-ligand interaction. Y398S binds to p-coumaric acid 4a with higher affinity than the wild-type enzyme, resulting in a shift in equilibrium toward favoring the productive coupling path instead of the path leading to wasteful flavin oxidation.